A Customizable Quantum-Dot Cellular Automata Building Block for the Synthesis of Classical and Reversible Circuits - Ahmed Moustafa; Ahmed Younes; Yasser F. Hassan (The Scientific World Journal)
Quantum-dot cellular automata (QCA) are nanoscale digital logic constructs that use electrons in arrays of quantum dots to carry out binary operations. In this paper, a basic building block for QCA will be proposed. The proposed basic building block can be customized to implement classical gates, such as XOR and XNOR gates, and reversible gates, such as CNOT and Toffoli gates, with less cell count and/or better latency than other proposed designs.